دور ممارسة الرياضة في تحسين جودة الحياة المرتبطة بالصحة - بن دادة سامي; Supervisor قارة سعيد (Mohamed Boudiaf University of M'sila, 2024)
الملخص: باللغة العربية: تهدف الدراسة إلى معرفة دور ممارسة الرياضة في تحسين جودة الحياة المرتبطة بالصحة لدى الأفراد ولهذا الغرض استخدمنا المنهج الوصفي على عينة متكونة من 200 شخص عاقل تتراوح أعمارهم ما بين 20 سنة إلى 50 سنة من بلدية العلمة ولاية سطيف تم اختيارها بشكل عشوائي، لجمع البيانات استخدمنا استمارة الاستبيان، بعد جمع النتائج ومعالجتها إحصائيا تم التوصل إلى النتائج لممارسة الرياضة دور في تحسين جودة الحياة المرتبطة بالصحة لدى الأفراد وهناك فروق دالة إحصائيا بين الممارسين والغير الممارسين. وعلى هذا الأساس أوصت الدراسة بضرورة تشجيع المجتمع على ممارسة الرياضية والتحسيس بأهميتها من خلال تنظيم التظاهرات الرياضية ونشر الوعي الثقافي لدور الرياضية في تحسين جودة الحياة المرتبطة بالصحة لدى الأفراد. عنوان الدراسة: دور ممارسة الرياضة في تحسين جودة الحياة المرتبطة بالصحة. أهداف الدراسة:  معرفة دورممارسة الرياضة في تحسين جودة الحياة المرتبطة بالصحة لدى الأفراد.  معرفة دور ممارسة الرياضة في تحسين الصحة البدنيةلدى الأفراد.  معرفة دور ممارسة الرياضة في تحسينالصحة النفسية لدى الأفراد.  معرفة إدا كان هناك فروق ذات دلالة إحصائية بين الممارسين والغير الممارسين للرياضة في جودة الحياة المرتبطة بالصحة لدى الأفراد. التساؤل العام الدراسة:  هل لممارسة الرياضة دور في تحسين جودة الحياة المرتبطة بالصحة لدى الأفراد؟ التساؤلات الجزئية:  هل ممارسة الرياضة تساهم في تحسينالصحة البدنية لدى الأفراد؟  هل ممارسة الرياضة تساهم في تحسين الصحة النفسية لدى الأفراد؟  هل توجد فروق ذات دلالة إحصائية بين الممارسين والغير الممارسين للرياضة في جودة الحياة المرتبطة بالصحة لدى الأفراد؟ الفرضية العامةللدراسة:  لممارسة الرياضة دور في تحسين جودة الحياة المرتبطة بالصحة لدى الأفراد. الفرضيات الجزئية:  ممارسة الرياضة تساهمفي تحسين الصحة البدنية لدى الأفراد.  ممارسة الرياضة تساهمفي تحسينالصحة النفسية لدى الأفراد.  توجد فروق ذات دلالة إحصائية بين الممارسين والغير الممارسين للرياضة في جودة الحياة المرتبطة بالصحة لدى الأفراد. المنهج المتبع في الدراسة: المنهج الوصفي. الأدوات المستخدمة في الدراسة: استمارة الاستبيان. الكلمات المفتاحية: بالعربية: الرياضة/ جودة الحياة /الصحة. بالإنجليزية: sports / quality of life / health. جاءهذاالبحث في فصول .  الفصل الأول:الإطار العام للدراسة.  الفصل الثاني:الرياضة والنشاط الرياضي.  الفصل الثالث: جودة الحياة.  الفصل الرابع:الإجراءات الميدانية للبحث.  الفصل الخامس: عرض وتحليل ومناقشة نتائج الدراسة.  الفصل السادس: الاستنتاجات والإقتراحات. من أهم النتائج الت يتوصل إليهاالباحث:  لممارسة الرياضة دور في تحسين جودة الحياة المرتبطة بالصحة لدى الأفراد.  ممارسة الرياضة تساهمفي تحسين الصحة البدنية لدى الأفراد.  ممارسة الرياضة تساهمفي تحسين الصحة النفسية لدى الأفراد.  توجد فروق ذات دلالة إحصائية بين الممارسين والغير الممارسين للرياضة في جودة الحياة المرتبطة بالصحة لدى الأفراد. أهم التوصيات:  تشجيع المجتمع على ممارسة الرياضية والتحسيس بأهميتها من خلال تنظيم التظاهرات الرياضية.  نشر الوعي بأهمية ممارسة الرياضة لدى الفئات المختلفة (الأطفال، الشباب، الشيوخ).  توعيةالمجتمع بممارسة الرياضة وزرع الثقافة الصحية فيهم.  نشر الوعي الثقافي لدور الرياضية في تحسين جودة الحياة المرتبطة بالصحة لدى الأفراد.  إجراءالمزيد من الدراسات والبحوث حول أهمية ممارسة الرياضية في تنمية مختلف الجوانب النفسية والاجتماعية والانفعالية.   Searchlight in English Faculty Institute of Sciences and Sports and Technical and PhysicalActivities Department: Order No:Sports training No. d 'registration:UN2801202322063080159 Searcher:Bendada Sami Publicly supported on: 20/06/2024 Title of the thesis (dissertation):The role of exercise in improving health-related quality of life. Language of the thesis: Arabic. Model of the thesis: Master. Country: REPUBLIC OF ALGERIA-M'SILA University: University of M'sila Surname and first name of the supervisor:Kara Said Grade: Doctor. Lecturer Number of pages: 76. Option: Summary: The Object of the study aims to identifyThe role of sports in improving health-related quality of life in individuals, for this purpose, we used the method DescriptiveOn a sample composed of200 sane people aged between 20 and 50 years from the municipality of El Eulma, Setif ProvinceChosen asrandom, and for data collection, we used a toolQuestionnaire, After collecting the results and having treated them statistically, we concludeSports have a role in improving the health-related quality of life of individuals, and there are statistically significant differences between those who practice sports and those who do not practice sports.On this basis, the study recommendedThere is a need to encourage society to practice sports and raise awareness of its importance by organizing sports events and spreading cultural awareness of the role of sports in improving the health-related quality of life of individuals. Title of the study:The role of exercise in improving health-related quality of life. The purpose of the study:  Knowing the role of exercise in improving individuals’ health-related quality of life.  Knowing the role of exercise in improving individuals’ physical health.  Knowing the role of exercise in improving the mental health of individuals.  Find out if there are statistically significant differences between those who practice sports and those who do not practice sports in the health-related quality of life of individuals.. Problem: General question:  Does exercise have a role in improving individuals’ health-related quality of life? Partial questions:  Does exercising contribute to improving individuals’ physical health?  Does exercising contribute to improving individuals’ mental health?  Are there statistically significant differences between practitioners and non-practitioners of sports in the health-related quality of life of individuals? Hypotheses: General hypothesis:  Exercising has a role in improving individuals’ health-related quality of life. Partial hypotheses:  Exercising contributes to improving the physical health of individuals.  Exercising contributes to improving the mental health of individuals.  There are statistically significant differences between those who practice sports and those who do not practice sports in the health-related quality of life of individuals. Key words:sports / quality of life / health. The most important results achieved are:  Exercise has a role in improving individuals’ health-related quality of life.  Exercising contributes to improving the physical and psychological health of individuals.  Exercising contributes to improving the mental health of individuals.  There are statistically significant differences between those who practice sports and those who do not practice sports in the health-related quality of life of individuals.
Keywords: الصحة; جودة الحياة; الرياضة